Neurodivergent Students in Regular EFL Classrooms - Elza, Meriyan (Verba: Journal of Applied Linguistics, 2024)
The number of students who are diagnosed as neurodivergent person or seem to have the symptoms has increased in regular classes, and English as a Foreign Language (EFL) classrooms are no exception. This study aims at explaining the condition of classroom atmosphere due to the presence of neurodivergent students, teachers’ viewpoint, parents’ perspective, and strategies in managing the classroom, and what experts say about this issue. This is a qualitative study by which the data were obtained from an observation and interview with the teachers from two branches of a language institution in West Sumatra. Based on the teachers’ viewpoint, the result showed that there were almost no significant barriers for neurodivergent students to understand the target language, but their presence disturbed the communicative task. Then, based on the parents’ perspective, there were parents who admitted the condition, and there were who did not. However, all parents wanted their children to go to the educational institution where diversity is accepted or just to be enrolled in a regular educational institution. Looking at this phenomenon from different perspectives hopefully lead to the idea of an appropriate approach for these students to integrate into the regular EFL classroom.